1994
DOI: 10.1007/bf02087768
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease and insulin-dependent diabetes mellitus

Abstract: We screened for celiac disease, by means of IgA class anti-endomysium antibodies (EmA), 383 consecutive adults with insulin-dependent diabetes mellitus (IDDM). Two control populations entered the study as well: 151 adults with biopsy proven celiac disease, as true positives; and 520 controls (healthy and diseased) as true negatives. IgA-EmA positivity was found in 145 of 151 (96%) celiac disease patients but in none of the controls (100% specificity). EmA were positive in 12 of 383 (3.13%) IDDM patients: 10 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…Others have previously shown no difference in growth parameters regardless of dietary compliance (20). Within case subjects, the start of a GFD resulted in further significant improvement in mean HbA 1c levels compared with pre-GFD, confirming findings of some studies (24,27) but not others (13,14,19,25). Furthermore, mean HbA 1c levels were also lower when compared with control subjects.…”
Section: Effect Of Gfdsupporting
confidence: 71%
See 1 more Smart Citation
“…Others have previously shown no difference in growth parameters regardless of dietary compliance (20). Within case subjects, the start of a GFD resulted in further significant improvement in mean HbA 1c levels compared with pre-GFD, confirming findings of some studies (24,27) but not others (13,14,19,25). Furthermore, mean HbA 1c levels were also lower when compared with control subjects.…”
Section: Effect Of Gfdsupporting
confidence: 71%
“…Some report short stature with no differences in weight (4,5,11,16), whereas others have shown no differences in height or weight (15)(16)(17)19,25). During the same period, HbA 1c levels were lower in case subjects despite no difference in Cpeptide levels.…”
Section: Effect Of Gfdmentioning
confidence: 99%
“…Similar observations have were on a gluten free diet, and who were re-biopsied, demonstrated a resolution of their abnormal small bowel been reported in other studies in Type 1 diabetes, 10,12 although others have reported a high frequency of mucosal appearances, confirming the diagnosis and the success of treatment. haematological and biochemical abnormalities including iron deficiency anaemia, low serum folate and ferritin All our subjects experienced difficulties adjusting to the gluten free diet and all required regular dietetic levels and hypertransaminaemia, 14,25,26 in association with the coeliac disease. It is known that a wide spectrum support and advice in the early stages.…”
Section: Height and Body Mass Index Sdsmentioning
confidence: 99%
“…Autoimmune polyglandular syndrome is a rare endocrine disorder comprising a combination of at least two of the following autoimmune endocrine disorders: Addison's disease, autoimmune thyroid diseases, hypoparathyroidism, type I diabetes, or primary gonadal failure (20,42,46,90). In addition, nonendocrine diseases that have been described in autoimmune polyglandular syndrome include mucocutaneous candidiasis, vitiligo, alopecia, pernicious anemia, autoimmune hepatitis, primary biliary cirrhosis, and intestinal malabsorption.…”
Section: Autoimmune Endocrine Disorders and CDmentioning
confidence: 99%